PELEPASAN KATION BASA PADA BAHAN PIROKLASTIK GUNUNG MERAPI - Novalia Kusumarini; Sri Rahayu Utami; Zaenal Kusuma (Jurnal Tanah dan Sumberdaya Lahan, 2014)
Mount Merapi is most active volcano and periodically erupted. The erupted materials are soil parent materials which rich of base cations that useful for plant growth. Leaching process was used as alternative approach to study base cations released. Leaching experiment used artificial rain water. The effort to reduce base cations leached and also increase base cations relesed was using chicken manure, leucana litters, and Arachis pintoi that used as cover crop as the treatment of experiment. The leaching experiment simulated 4 years rainfall intensity. After incubation for 96 days (4 years rainfall simulation), addition of chicken maure and leucana litters decreased base cations leached in Mount Merapi pyroclastic materials, except for K+ by 16%. Planting Arachis pintoi decrease base cations leached in Mount Merapi pyroclastic materials by 13% but did not increase base cations released.Key words: pyroclastic, leaching, base cations